Coupling and optimisation of online nuclear magnetic resonance spectroscopy and mass spectrometry for process monitoring to cover the broad range of process concentration. (5th August 2016) - Blanazs, Alexander; Bristow, Tony W. T.; Coombes, Steven R.; Corry, Tom; Nunn, Mike; Ray, Andrew D.
Abstract : Real time online monitoring of chemical processes can be carried out by a number of analytical techniques, including optical and vibrational spectroscopies, nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS). As each technique has unique advantages and challenges, combinations are an attractive option. The combination of a 500‐MHz 1 H NMR and a small footprint mass spectrometer to monitor a batch reaction at process concentration was investigated. The mass spectrometer was coupled into the flow path of an online reaction monitoring NMR. Reaction mixture was pumped from a 100‐ml vessel to an NMR flow tube before returning to the vessel. Small aliquots were diverted into a sampling make‐up flow using an active flow splitter and passed to the mass spectrometer. Advantages of the combination were observed. 1 H NMR was ideal for quantitation of high level components, whereas MS showed a greater capability for detecting those at low level. In preliminary experiments MS produced a limited linear relationship with concentration (0.02% to 2% relative concentration, 0.01 mg/ml–1.25 mg/ml), because of signal saturation at the higher concentrations. NMR was unable to detect components below 0.1% relative to concentration maximum. Optimisation of sample transfer to the MS extended the linearity to 10% relative to the concentration maximum. Therefore, the combination of online NMR and MS allows both qualitative and quantitative analysis of reaction components over the full process range. The application of the combination was demonstrated by monitoring a batch chemical reaction and this is described. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The combination of a 500‐MHz 1 H NMR and a small footprint mass spectrometer to monitor a batch reaction at process concentration was investigated. Advantages of the combination were observed. 1 H NMR was ideal for quantitation of high level components, whereas MS showed a greater capability for detecting those at low level. The application of the combination was demonstrated by monitoring a batch chemical reaction and this is described.